A novel method for rapidly calculating explosion dynamic displacement response of reticulated shell structure based on influence surfaces. Issue 6 (April 2020) - Chen, Xin; Gao, Xuanneng; Lin, Xiang; Liu, Jingliang; Le, Lihui
In order to analyse the mechanical behaviour of a reticulated shell structure under explosive load, a novel method was proposed to calculate the dynamic displacement response of the cylindrical reticulated shell structure by using the influence surface in this article. First, the theory of the dynamic influence line was developed and the consistency between the dynamic influence lines and the static ones was verified. Then, based on the theory of the dynamic influence line and for the simplified calculation of dynamic responses, the dynamic influence lines of a simply supported beam were simplified as the static ones multiplied by the dynamic amplification factor β . And then the explosion dynamic responses of the beam could be fast calculated using the influence lines. The extended application of the above method to single-layer cylindrical reticulated shell was the influence surface method. The results of numerical examples showed that the nodal displacements of the structure obtained by using the influence surface method agreed well with those obtained by using ANSYS/LS-DYNA. The research results also indicated that the influence surface method was applicable to the node displacement calculation of the structure under three different conditions, including the centre node of the symmetrical structure, the arbitrary nodes (excluding those near the supports) of symmetrical structure under symmetrical loads and the arbitrary nodes of arbitrary structures in which the load holding time is much longer than the natural vibration period of structure. The proposed approach could reduce the computation cost for analysing the explosion dynamic response of the reticulated shell structure, thereby providing a more effective method for the anti-explosion design of reticulated shell structures.